Addressing Self-Stigma in Fibromyalgia Using Pain Neuroscience Education: An Occupational Therapy Case Study. - Davis, Christine; Gillard, Marian (Occupational Therapy in Mental Health)
The symptoms of fibromyalgia can be misperceived because they are often visibly undetectable, thereby leaving persons with fibromyalgia exposed to others' incorrect understanding of their experience and physical capabilities. Persons with fibromyalgia may experience stigma, when nobody understands the condition or how it affects their daily occupations. This retrospective case study describes how occupational therapy, as part of a biopsychosocial and multidisciplinary team approach, can use pain neuroscience education as an effective treatment strategy for fibromyalgia and discusses the benefits of an educational approach to improve our understanding of fibromyalgia, as well as decrease self-stigma and increase occupational performance.